Tumor regression grading after preoperative chemoradiotherapy for locally advanced rectal carcinoma revisited: updated results of the CAO/ARO/AIO-94 trial - Fokas, Emmanouil; Liersch, Torsten; Fietkau, Rainer; Hohenberger, Werner; Beissbarth, Tim; Hess, Clemens; Becker, Heinz; Ghadimi, Michael; Mrak, Karl; Merkel, Susanne; Raab, Hans-Rudolf; Sauer, Rolf; et al. (Journal of Clinical Oncology, 2014)
We previously described the prognostic impact of tumor regression grading (TRG) on the outcome of patients with rectal carcinoma treated with preoperative chemoradiotherapy (CRT) in the CAO/ARO/AIO-94 trial. Here we report long-term results after a median follow-up of 132 months.TRG after preoperative CRT was determined in 386 surgical specimens by the amount of viable tumor cells versus fibrosis, ranging from TRG 4 (no viable tumor cells) to TRG 0 (no signs of regression). Clinicopathologic parameters and TRG were correlated to the cumulative incidence of local recurrence, distant metastasis, and disease-free survival (DFS).Ten-year cumulative incidence of distant metastasis and DFS were 10.5% and 89.5% for patients with TRG 4 (complete regression), 29.3% and 73.6% for TRG 2 and 3 (intermediate regression), and 39.6% and 63% for TRG 0 and 1 (poor regression), respectively (P = .005 and P = .008, respectively). On multivariable analysis, residual lymph node metastasis (ypN+) and TRG were the only independent prognostic factors for cumulative incidence of distant metastasis (P < .001 and P = .035, respectively) and DFS (P < .001 and P = .039, respectively), whereas local recurrence was significantly affected by ypN status (P < .001) and lymphatic invasion (P = .026).Complete and intermediate tumor regressions were associated with improved long-term outcome in patients with rectal carcinoma after preoperative CRT independent of clinicopathologic parameters. This classification system needs to be prospectively tested in multiple data sets to validate its reproducibility in a wider setting.
EVALuna2:15168